Analisis Pengaruh Dana Pihak Ketiga, Pembiayaan Mudharabah dan Musyarakah terhadap Profitabilitas Bank Syariah - Adi Saputra, Septa; Ira Khumaira, Kamala; Handayani, Krisnawuri; Sulistyorini, Ery (University of Merdeka Malang, 2022)
The purpose of this study was to determine how the effectiveness of Third Party Funding (TPF), mudharabah financing, and musyarakah financing on the profitability of Islamic banks. The data collection in this study came from the annual financial statements of eight Islamic banks in Indonesia. This study uses a partial regression analysis technique (Partial Least Square/PLS) through WarpPLS 7.0 software. The results of the study indicate that TPF financing as measured by FDR (Finance Deposit Ratio) and sharia mudharabah financing has a significant positive effect on profitability. While the influence of Islamic musharaka financing has a significant negative effect on profitability.